2021
DOI: 10.1186/s12911-021-01447-4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effects of electronic health records system adoption on the performance of Malaysian health care providers

Abstract: Background The Ministry of Health of Malaysia has invested significant resources to implement an electronic health record (EHR) system to ensure the full automation of hospitals for coordinated care delivery. Thus, evaluating whether the system has been effectively utilized is necessary, particularly regarding how it predicts the post-implementation primary care providers’ performance impact. Methods Convenience sampling was employed for data coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 41 publications
2
13
0
2
Order By: Relevance
“…Additionally, all the factors in our instrument are positively and signi cantly correlated with each other, and the order of the correlation strength of the independent variables (SQ, IQ, ISQ, ORG, ENV, US) with the dependent variable (CP) was the human factor: user satisfaction (US), the organizational factor (ORG), the technological factor (SQ, IQ, ISQ), and the environmental factor (ENV). These ndings highlight the importance of the human factor in the successful adoption of the EHR system in Morocco hospitals, which corroborates the conclusion of Salleh et al [59], who showed that improving the quality of healthcare professionals' knowledge positively impacts their performance when using EHR systems. Similarly, studies by Garcia-Smith,D., & Effken [60] and Yu & Qian [61] concluded that healthcare staff satisfaction with clinical information system use is the best predictor of perceived net bene ts from EHR adoption.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Additionally, all the factors in our instrument are positively and signi cantly correlated with each other, and the order of the correlation strength of the independent variables (SQ, IQ, ISQ, ORG, ENV, US) with the dependent variable (CP) was the human factor: user satisfaction (US), the organizational factor (ORG), the technological factor (SQ, IQ, ISQ), and the environmental factor (ENV). These ndings highlight the importance of the human factor in the successful adoption of the EHR system in Morocco hospitals, which corroborates the conclusion of Salleh et al [59], who showed that improving the quality of healthcare professionals' knowledge positively impacts their performance when using EHR systems. Similarly, studies by Garcia-Smith,D., & Effken [60] and Yu & Qian [61] concluded that healthcare staff satisfaction with clinical information system use is the best predictor of perceived net bene ts from EHR adoption.…”
Section: Discussionsupporting
confidence: 88%
“…However, a recent study by Salah et al [59], which focused on evaluating the effect of adopting an EHR system on the performance of Malaysian healthcare professionals, only emphasized ve constructs (system quality, records quality, service quality, knowledge quality, and effective use) that have a signi cant impact on healthcare providers' performance.…”
Section: Discussionmentioning
confidence: 99%
“…The system applicability and record quality are also important factors that affect the acceptance of the ESR system by clinicians or users such as the CRC. We chose the questionnaire items based on the items on the EHR scale that were used in Salleh et al [ 20 ]. The questionnaire designed by Salleh et al contains six subcategories.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, an efficacious health strategy necessitates monitoring technology use and the behaviour of users and making improvements based on the results obtained (Falchook et al, 2015). According to Salleh, Abdullah, and Zakaria (2021), assessing the performance of an EHR system is crucial yet complex. Recent literature also indicates that there is no standard method for correlating an effective EHR system, as different healthcare institutions have unique organizational structures, workflow processes, and employee expectations that substantially affect how the EHR system is used within the organisation.…”
Section: Literature Reviewmentioning
confidence: 99%